2016
DOI: 10.1504/ijil.2016.076673
|View full text |Cite
|
Sign up to set email alerts
|

The role of expected years of schooling among life expectancy determinants

Abstract: Increasing life expectancy at birth is a huge achievement for a society; however it also brings many challenges and requires a society to constantly adapt to demographic consequences. In our research, we investigate life expectancy determinants and the role of a country's education level among them. Using multiple regression analysis on cross-section data of 187 countries around the world we confirm our main research thesis that a country's education level is an important determinant of life expectancy at birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…Hasil pengujian regresi ini sesuai dengan beberapa penelitian yang menyatakan bahwa angka harapan hidup berpengaruh secara negatif terhadap kemiskinan (Bintang and Woyanti, 2018;Efendi, Indartono and Sukidjo, 2019;Suryandri, 2018) dan pendidikan berpengaruh secara positif dengan kesehatan (Cohen, 2014;Novak, Anica;Cepar, Ziga & Trunk, 2014). Indikator kemiskinan ini sangat di pengaruhi oleh tingkat kesehatan dan status gizi yang menunjang angka harapan hidup (Tisniwati, 2012).…”
Section: Regresi Berganda (Multiple Regressions)unclassified
“…Hasil pengujian regresi ini sesuai dengan beberapa penelitian yang menyatakan bahwa angka harapan hidup berpengaruh secara negatif terhadap kemiskinan (Bintang and Woyanti, 2018;Efendi, Indartono and Sukidjo, 2019;Suryandri, 2018) dan pendidikan berpengaruh secara positif dengan kesehatan (Cohen, 2014;Novak, Anica;Cepar, Ziga & Trunk, 2014). Indikator kemiskinan ini sangat di pengaruhi oleh tingkat kesehatan dan status gizi yang menunjang angka harapan hidup (Tisniwati, 2012).…”
Section: Regresi Berganda (Multiple Regressions)unclassified
“…There were five studies (#3, 22, 34, 37, and 44) examining the relationships between population growth and LE. Novak et al 15 found that the urban population had a positive impact in LE according to 187 countries in the year 2010 (β = 0.070, P = .012) and 2005 (β = 0.061, P = .030). Ye et al 25 found that the ageing index showed a significant relation on LE in China ( r = 0.980, P < .05) and the United States ( r = 0.834, P < .05).…”
Section: Review Findingsmentioning
confidence: 99%
“…Clark and Peck 21 found that women's status of labor force ratio (β = 0.040, P < .05) expanded the gender gap in LE while women's status of parliament ratio (β = −0.020, P < .05) reduced the gender gap in LE. Novak et al 15 showed that gender inequality has a significant negative impact on LE in 2010 (β = −0.136, P = . 16 showed that there was a significant positive effect of GDP toward LE (β = 0.039, P = .042) and (β = 0.0739, P < .001).…”
Section: Socioeconomic Status (Sesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although relevant and popular, research report a dearth of well-structured entrepreneurship programs and challenges for educators to design appropriate education strategies in order to develop quality entrepreneurship courses (Matlay, 2006;Novak et al, 2016;Law et Breznik, 2017). On a semi-systematic literature review, Mwasalwiba (2010) iden-tified two main groups in which most authors categorize teaching methods: "traditional methods" (or lecture-based passive methods), and "innovative methods" (also known as active methods).…”
Section: Theoretical Backgroundmentioning
confidence: 99%